2022
DOI: 10.30525/2256-0742/2022-8-2-83-90
|View full text |Cite
|
Sign up to set email alerts
|

International Financial Activities: Accounting, Taxation and Insurance

Abstract: The need for the study of international financial relations is justified by the lack of modern scientific discourses on the methods of regulation of financial tensions in the new epidemiological conditions of business environment and appropriate methodology to manage the level of rejection of players in the international financial market. The purpose of this study is to find points of contact between accounting, tax and insurance accounting in the development of joint measures to overcome global financial risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…1. Integrated accounting system with transactional management and strategic accounting Source: developed by the authors based on [10] But not always existing or foreign accounting and financial mechanisms, as the practice of the author's studies [15,16,17,18] have shown, work in the conditions of Ukraine. For the modern period, the most relevant mechanisms are those that transform the debt model of deficit financing of the economy into the necessary attraction of the necessary financial resources to ensure production, solve the problem of quality of life and economic growth [19].…”
Section: Resultsmentioning
confidence: 99%
“…1. Integrated accounting system with transactional management and strategic accounting Source: developed by the authors based on [10] But not always existing or foreign accounting and financial mechanisms, as the practice of the author's studies [15,16,17,18] have shown, work in the conditions of Ukraine. For the modern period, the most relevant mechanisms are those that transform the debt model of deficit financing of the economy into the necessary attraction of the necessary financial resources to ensure production, solve the problem of quality of life and economic growth [19].…”
Section: Resultsmentioning
confidence: 99%